Reviews on Selected Topics of Telomere Biology - Li, Bibo; Li, Bibo (IntechOpen, 2012)
Telomeres, located at the ends of linear chromosomes, are essential for genome stability and integrity. Advances in telomere researches have linked telomere dysfunction with cellular aging and a number of age-related human diseases. Recent studies further expanded our knowledge of telomere functions - telomeres are shown to be important for microbial pathogen virulence and telomere proteins have important non-telomeric cellular functions. This book includes current opinions on selected aspects of telomere research and their implication, in hope to help us focus better on future studies and enhance our research progress.
English
Keywords: Medical genetics; Medical genetics